2018
DOI: 10.1055/s-0038-1666782
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Extensive Ossification of the Posterior Petroclinoid Ligament: An Anatomical Case Report and Literature Review

Abstract: Because the ossification of the posterior petroclinoid ligament may be considered a factor influencing diagnostic and surgical procedures, neurosurgeons and neuroradiologists should be aware of this variation. Ossification of the posterior petroclinoid ligament may also potentially result in greater susceptibility of the oculomotor nerve to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Such variation was observed in our material in two cases in which the presence of ossification within the dura covering inferomedial triangle was confirmed histologically. Similar findings have also been described in anatomical and radiographic reports [ 14 , 15 , 16 , 17 , 18 , 19 ]. Touska et al [ 18 ] concluded that ligamentous skull base mineralizations are relatively common findings on CT scans.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Such variation was observed in our material in two cases in which the presence of ossification within the dura covering inferomedial triangle was confirmed histologically. Similar findings have also been described in anatomical and radiographic reports [ 14 , 15 , 16 , 17 , 18 , 19 ]. Touska et al [ 18 ] concluded that ligamentous skull base mineralizations are relatively common findings on CT scans.…”
Section: Discussionsupporting
confidence: 90%
“…Touska et al [ 18 ] concluded that ligamentous skull base mineralizations are relatively common findings on CT scans. In the majority of cases, intracranial calcifications or ossifications are not accompanied by any detectable pathology [ 14 , 19 ]. However, mineralization of skull base ligaments can occur as a result of an interplay between a broad range of factors, including genetics, metabolic abnormalities and mechanical stress [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissecting procedure was designed and performed according to previously described protocols [6,1820]. The orbit was carefully opened through removal of its entire superior wall (the orbital roof) using bone chisel and Luer bone rongeur.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was based on the additional removal of the wedge-shaped part of the occipital squama. This access not only protects the cranial nerves, which allows obtaining a good quality of specimens [21,59,61] but also prevents accidental damage to the brainstem, which is crucial especially when using the Klingler's method. The access may be extended by removal of the vertebral arches (vertebral pedicles must be carefully chiseled), which allows obtaining a complete specimen of the brain and spinal cord.…”
Section: Researchers Demonstrated Structuresmentioning
confidence: 99%